2014
DOI: 10.4149/gpb_2013065
|View full text |Cite
|
Sign up to set email alerts
|

β3-Adrenoceptor-mediated responses in diabetic rat heart

Abstract: β3-adrenoceptors mediate negative inotropic effect in contrast to classical β1- and β2-adrenoceptors. Cardiac β3-adrenoceptors are upregulated in experimental diabetes. Thus, cardiodepressant effect mediated by β3-adrenoceptors has been proposed to contribute to the impaired cardiac function in this pathology. In our study, we investigated the influence of streptozotocin-diabetes on cardiac contractility to β3-adrenoceptors stimulation by using Langendorff-perfused rat hearts. BRL 37344, a selective β3-adrenoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 38 publications
4
14
0
Order By: Relevance
“…Our findings are in line with the previous studies on ß3-AR-mediated-vasorelaxation and the localization of the receptor [9,10,23]. We proposed that the response may be different in diabetic aorta since ß3-AR-mediated cardiac responses have been found to be changed in diabetes [24,25]. Furthermore, the expression of this subtype is upregulated in cardiac pathologies such as diabetes or heart failure [24][25][26][27][28][29].…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are in line with the previous studies on ß3-AR-mediated-vasorelaxation and the localization of the receptor [9,10,23]. We proposed that the response may be different in diabetic aorta since ß3-AR-mediated cardiac responses have been found to be changed in diabetes [24,25]. Furthermore, the expression of this subtype is upregulated in cardiac pathologies such as diabetes or heart failure [24][25][26][27][28][29].…”
Section: Discussionsupporting
confidence: 91%
“…These data have led to the hypothesis that β 3 ‐adrenoceptor agonists could be useful in patients with heart failure (Rasmussen, Figtree, Krum, & Bundgaard, ). An up‐regulation of cardiac β 3 ‐adrenoceptor expression at the mRNA level has also repeatedly (Amour et al, , ; Dinçer et al, ; Kayki‐Mutlu, Arioglu Inan, Ozakca, Ozcelikay, & Altan, ) but not unequivocally (Haley, Thackeray, Kolajova, Thorn, & DaSilva, ; Jiang et al, ) been observed in animal models of diabetes or of hypothyroidism (Arioglu, Guner, Ozakca, Altan, & Ozcelikay, ). Nevertheless, β 3 ‐adrenoceptors were also reported to be down‐regulated in an animal model of colitis, where treatment with an agonist improved symptoms and reversed the down‐regulation (Vasina et al, ).…”
Section: Evidence Of Synthesis and Conclusionmentioning
confidence: 97%
“…* P < 0.05, *** P < 0.001, control versus diabetic; # P < 0.05, ## P < 0.01, diabetic versus insulin‐treated diabetic; ɸ P < 0.05, comparison of the different concentration–response curves by two‐way ANOVA. Adapted with permission from (Kayki‐Mutlu et al, )…”
Section: Expression and Function Of β3‐adrenoceptors In Normal Heartmentioning
confidence: 99%
“…Studies in several, but not all animal models of diabetes, have found increased cardiac β 3 ‐adrenoceptor expression at the mRNA and/or protein level (Table ). Thus, an up‐regulation was found in rats treated with streptozotocin, a type 1 diabetes model, at the mRNA (Dinçer et al, ; Kayki‐Mutlu et al, ) and protein level (Amour et al, ; Amour et al, ; Dinçer et al, ). One of these studies also demonstrated that treatment with insulin restored β 3 ‐adrenoceptor expression to normal levels (Dinçer et al, ).…”
Section: Alterations In Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation